Anterior Cruciate Ligament Repair with Suture Augmentation for Proximal Avulsion Injuries - Wiemi A. Douoguih, M.D; Ralph T. Zade, M.D; Blake M. Bodendorfer, M.D; Yalda Siddiqui, B.S; Andrew E. Lincoln, D.P.H (Elsevier, 2020)
Purpose: To assess failure rate, outcomes, and patient satisfaction in patients who underwent anterior cruciate ligament (ACL) repair with suture augmentation for clinical instability and proximal avulsion of the ACL. Methods: We retrospectively reviewed consecutive suture-augmented ACL repairs performed by a single surgeon between January 2014 and June 2016 for proximal ACL avulsion. Patients were included if they were at least 24 months postoperative from repair surgery. Patients were excluded from the study if they underwent primary ACL reconstruction instead of repair or if they had a concomitant multiligamentous knee injury. Knee Injury and Osteoarthritis Outcome Score (KOOS), visual analog scale (VAS), Veterans RAND-12 (VR-12), Marx Activity, and Single Assessment Numeric Evaluation data were collected. Results: Of 172 patients who underwent ACL surgery between January 2014 and June 2016, 28 (16%) with Sherman type I or II ACL tears or high-grade partial avulsion with clinical instability underwent ACL repair with suture augmentation. One patient was not available for follow-up. The 27 patients were age 27.4 ± 8.6 years, 18 males (66.7%), and 2.8 ± 0.7 years follow-up (range, 2.0-3.8 years). Of these 27 patients, 4 recurrent ACL injuries (14.8%) required revision to reconstruction. The remaining 23 patients had successful ACL repair with no clinical instability and no subjective complaints at final follow-up. Final scores were KOOS 83.7 ± 12.8, Marx 8.6 ± 4.0, VAS 1.1 ± 1.8, physical VR-12 53.6 ± 5.2, mental VR-12 53.1 ± 8.1, and Single Assessment Numeric Evaluation 83.0 ± 12.9. In the 11 patients with baseline data, significant improvements were observed in composite KOOS (50.4 ± 11.5 to 85.7 ± 8.4; P < .001; VAS: 3.9 ± 2.6 to 0.8 ± 0.8; P = .002; and physical VR-12: 39.9 ± 6.5 to 55.5 ± 3.3; P < .001). All 11 patients (100%) met or exceeded the KOOS composite minimum clinically important difference (mean 34.0 increase). Conclusions: In patients with proximal ACL avulsion, arthroscopic primary ACL repair with suture augmentation demonstrated high functional outcome and improved patient-reported outcomes at 2-year follow-up. The rate of graft failure was 15%. Level of Evidence: Level IV, therapeutic case series.